Reconstruction of Late Pleistocene Paleoenvironments Using Bulk Geochemistry of Paleosols from the Lake Victoria Region - Beverly, Emily J.; Peppe, Daniel J.; Driese, Steven G.; Blegen, Nick; Faith, J. Tyler; Tryon, Christian A.; Stinchcomb, Gary E. (Frontiers in Earth Science, 2017)
The impact of changing environments on the evolution and dispersal of Homo sapiens is highly debated, but few data are available from equatorial Africa. Lake Victoria is the largest freshwater lake in the tropics and is currently a biogeographic barrier between the eastern and western branches of the East African Rift. The lake has previously desiccated at ~17 ka and again at ~15 ka, but little is known from this region prior to the Last Glacial Maximum. The Pleistocene terrestrial deposits on the northeast coast of Lake Victoria (94 to 36 ka) are ideal for paleoenvironmental reconstructions where volcaniclastic deposits (tuffs), fluvial deposits, tufa, and paleosols are exposed, which can be used to reconstruct Critical Zones (CZ) of the past (paleo-CZs). The paleo-CZ is a holistic concept that reconstructs the entire landscape using geologic records of the atmosphere, hydrosphere, lithosphere, biosphere, and pedosphere (the focus of this study). New paleosol-based mean annual precipitation (MAP) proxies from Karungu, Rusinga Island, and Mfangano Island indicate an average MAP of 750108 mm yr-1 (CALMAG), 800182 mm yr-1 (CIA-K), and 1010228 mm yr-1 (PPM1.0) with no statistical difference throughout the 11 m thick sequence. This corresponds to between 54 and 72% of modern precipitation. Tephras bracketing these paleosols have been correlated across seven sites, and sample a regional paleo-CZ across a ~55 km transect along the eastern shoreline of the modern lake. Given the sensitivity of Lake Victoria to precipitation, it is likely that the lake was significantly smaller than modern between 94 ka and 36 ka. This would have removed a major barrier for the movement of fauna (including early modern humans) and provided a dispersal corridor across the equator and between the rifts. It is also consistent with the associated fossil faunal assemblage indicative of semi-arid grasslands. During the Late Pleistocene, the combined geologic and paleontological evidence suggests a seasonally dry, open grassland environment for the Lake Victoria region that is significantly drier than today, which may have facilitated human and faunal dispersals across equatorial East Africa.